PENGARUH MANAJEMEN LABA, RISIKO PASAR, KOMITE AUDIT, AUDIT EKSTERNAL, DAN STRUKTUR KEPEMILIKAN TERHADAP NILAI PASAR (Studi Empiris Pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Tahun 2011-2013) - Muhammad Baru Herman; Agus Purwanto (Diponegoro Journal of Accounting, 2015)
This study used an independent variable earnings management, market risk, audit committee, external audit, and ownership structure to analyze its effect on the market value as the dependent variable, using firm size, firm growth, and leverage as control variable. Measurement of market value used Feltham Ohlson model to determine the estimated market price of the firm.            The population of this study is 37 samples from manufacturing firms that listed in Indonesian Stock Exchange (IDX) during 2011 to 2013. The sampling method used for this study is purposive sampling. Type of data used is secondary data. Data analysis used descriptive statistics, classical assumption test, and multiple linear regression analysis.            The result of this study showed that earnings management, market risk, and external audit significantly influence to the market value. Meanwhile, audit committee, ownership structure (both institutional and managerial) had no significant effect to the market value.